Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 40



Work Step by Step

$(fg)(x)=f(x)g(x)$ $(fg)(-3)=f(-3)g(-3)$ First, find $f(-3)$ and $g(-3)$. $f(-3)=(-3)^{2}+4\times(-3)=9-12=-3$ $g(-3)=2-(-3)=2+3=5$ Then, multiply them. $(fg)(-3)=f(-3)g(-3)=-3\times5=-15$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.